Water Budgets of Tropical Cyclones through a Lagrangian Approach: A Case of Study of Hurricane Irma (2017) - Albenis Pérez-Alarcón; Raquel Nieto; Luis Gimeno; José C. Fernández-Alvarez; Patricia Coll-Hidalgo; Rogert Sorí (Environmental Sciences Proceedings, 2021)
This study examined the water budget of Hurricane Irma (2017) through a Lagrangian approach. To identify the moisture sources for the Hurricane Irma genesis and intensification the particle dispersion model FLEXPART was used. The North Atlantic Ocean between 15° and 30° North latitude and the South Atlantic Ocean were identified as the main moisture sources for Irma development. From the perspective of the water budget, the maximum accumulated precipitation along Irma’s trajectory coincides with the maximum water budget efficiency, which suggests that total precipitation depends largely on the water vapour supplied, rather than the storm intensity. Furthermore, the moisture supply from the surface under the area delimited by hurricane size is small, thus, the water vapour supply from the environment through the secondary circulation transports more moisture inward.